HUKUM KEPEMIMPINAN WANITA DALAM PEMERINTAHAN/NEGARA - Salman Salman (AL-ILMU, 2022)
Barriers that arise from women's leadership, among others, in terms of leadership is the ability to influence other people, so that person behaves and acts according to the leader's goals. The most important thing about leadership is the influence, style, or method of influencing other people and the effectiveness of the power of a leader. In the leadership of women in government, some scholars do not allow women to become leaders with the arguments used in Surah An-Nisa' verse 34 and hadith narrated by Abu Bakra. And the scholars also gave reasons why women should not be leaders, among others: Female leaders must be detrimental, Women lack reason and religion, Women when praying in congregation occupy the last row, Women cannot marry themselves, but must be with a guardian, Women according to their nature tends to decay, and women experience menstruation, pregnancy, childbirth, and breastfeeding. But there are also scholars who allow women to be leaders.